Front Cover Image. (28th January 2021) - Shi, Kaiyun; Wen, Jianxia; Zeng, Jinhao; Guo, Yaoguang; Hu, Jike; Li, Cong; Zhao, Yanling; Ma, Xiao
Abstract : The cover image is based on the Review Preclinical evidence of Yinchenhao decoction on cholestasis: A systematic review and meta‐analysis of animal studies by Kaiyun Shi et al., https://doi.org/10.1002/ptr.6806 . Abstract : The cover image is based on the Review Preclinical evidence of Yinchenhao decoction on cholestasis: A systematic review and meta‐analysis of animal studies by Kaiyun Shi et al., https://doi.org/10.1002/ptr.6806 .